Downstream effects of diversion dams on riparian vegetation communities in the Routt National Forest, Colorado - Caskey, Simeon Tadgerson, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Bledsoe, Brian, committee member; Merritt, David, committee member (Colorado State University. Libraries, 2013)
Diversions are ubiquitous throughout the American west, with over 68000 known in Colorado alone. Diversions vary greatly in their structure and ability to extract water, but overall they can alter important components of the flow regime, affecting the magnitude and duration of baseflows and flooding. Riparian plant communities have adapted to unique hydrologic and geomorphic conditions existing in the areas subject to fluvial processes. My study used vegetation and geomorphic data from low-gradient (≤3%) streams, in the Rocky Mountains of north-central Colorado, above 2440 m. Data were collected at 32 reaches, totaling 16 paired upstream and downstream sites, to infer the impact of diversion-induced flow alteration on riparian vegetation communities. Vegetation data were collected using the line-point intercept method along transects oriented perpendicular to the channel, from bankfull to 5-10 meters away, totaling 100 sampling points per reach. Topographic data were associated with each sampling point, to analyze differences in lateral and vertical zonation of communities between upstream and downstream reaches. Vegetation data were analyzed using traditional biological diversity metrics, richness, evenness and diversity, as well as multivariate community analysis using ANOSIM, MRPP, and permanova. Across all data points, field observations indicate evenness increased downstream from diversions, through decreased frequency of hydrophytic, wetland indicator functional species groupings, and increase in frequency of several upland indicator species. Regarding elevation, immediately above the channel no differences were observed between communities, but at 1 m above the channel increase in upland species and decrease in wetland species downstream of diversion became apparent. Logistic regression supports this, indicating probability of occurrence for upland species downstream of diversion increases at a greater rate beginning around 0.5 m above active channel. Related to distance, nearest the channel no compositional differences were observed, but with increasing distance from channel decreased wetland and increased upland species relative frequency were observed downstream of diversion. Fluvial surface analyses, which are related to distinct hydrologic and geomorphic processes, also indicated composition shift as a function of diversion. Floodplains had significantly lower relative frequency of wetland species grouping, whereas low terraces had both increased upland and decreased wetland species relative frequency downstream of diversion. The findings of my study imply that riparian plant communities along low-gradient reaches in montane environments in the Rocky Mountains of Colorado are being impacted by diversion-induced flow alteration, in general having a reduced frequency of hydrophytic, wetland species, and encroachment of non-hydrophytic, upland species.